Dynamic Analysis of a Rolling Bearing Cage with Respect to the Elastic Properties of the Cage for the Axial and Radial Load Cases - Robert Kohar; Slavomir Hrcek (Communications, 2014)
The aim of this paper is to detail the creation of a large tapered roller bearing model with flexible body cages in the Adams program suite for subsequent dynamic analysis and to obtain information about kinematic and dynamic relationships of steel and plastic cages under various operating conditions. The bearing model was made to closely resemble its real-life counterpart, which allows us to estimate load conditions, dynamic conditions of individual bearing parts and interactions between them.